Analisis Faktor-Faktor Kinerja Operasional Pemeliharaan Aset Fisik Pengolahan Instalasi Air Limbah di Kota Sungai Penuh - Susanto, Arry; Mulyani, Rini; Zulherman, Zulherman (Jurnal Civronlit Unbari, 2024)
Infrastructure Assets and Facilities are basic requirements for economic development and growth, both are not simple objects and require huge costs. In addition, the relationship between the two with the aspect of election is very important. Because there is no maintenance of the physical assets of communal WWTP in Sungai TFull City, often the units on the WWTP are damaged so that it can hinder the wastewater treatment process. The less optimal performance of WWTP is influenced by human resources, machinery and equipment, as well as problems in the series of WWTP processes. The research method that is used is a quantitative method with the distribution of questionnaires to the respondents involved. The purpose of this study is to identify the factors and dominant factors of the operational performance of the maintenance of physical assets of wastewater treatment plants in Sungai TFull City, as well as to provide strategic strategies to improve the maintenance operations of physical assets of wastewater treatment plants in Sungai TFull City. The results of the research conducted are 5 factors in the operational performance of the maintenance of physical assets of wastewater treatment plants in Sungai TFull City, which consists of cost factors, human resource factors, work method factors, and equipment factors.